Occurrence of nitrogen-fixing cyanobacteria during different stages of paddy cultivation (Bangladesh Journal of Plant Taxonomy, 2011)
Not availableKeywords: Cyanobacteria; Diversity; Nitrogen-fixing; Rice fields; North Bihar.DOI: 10.3329/bjpt.v18i1.7842Bangladesh J. Plant Taxon. 18(1): 73-76, 2011 (June)